Kyrkorummets påsksymbolik - Jonsson, Hedvig Brander (Svenskt gudstjänstliv, 1997)
The idea that a building and its elements may have meanings surpassing the constructive and functional aspects is probably of about the same age as human culture. There may also be symbolic dimensions available to who ever is willing to realize them. This is especially applicable to church architecture. As early as during the first part of the Christian era, there were signs and symbols expressing that a building was to be regarded as the House of the Lord. The intention behind this study is to discern the symbolic elements in church architecture and decoration which express the message of Easter, i.e. of triumph and resurrection. These symbolic elements are not to be wholly separated from those expressing the passion and sacrifice of Our Lord. Instead they are closely related. Moreover, the message of Easter is the pre-requisite for Christian life, for the church building, and for the liturgy - and it seems that it has not been necessary to underline Easter symbols as such. The Motif of Triumph and its Origin The first Christian emperor, Constantine the Great (306-25) ordered al most fervently the erection of monumental churches throughout his empire, principally in Rome, in The holy land and in Constantinople. Beside their huge dimensions, these churches are characterized by the shape of the wall between the nave and the choir as a triumphal arch, an architectural structure with an unmistakable triumphal character, the way it had been used in order to glorify victorious emperors for almost three centuries. The victor now to be honoured was Christ who had conquered death and made his congregation triumph over its enimies, according to the Constatinian inscription - a quotation from his inauguration speech - at the top of the triumphal arch in Old St. Peter’s; saying that the world, led by Christ, has triumphally reached the stars, and, accordingly, the victorious Constantine erected this church to honour Him.The basilica, “inherited” from late antique, imperial town planning, and transformed for ecclesiastical use by Constatine and his architects, became the most important model for monumental church buildings until modern time. Spacious, lighted by generous rows of windows, with a distinct direction towards the most sacred part of the room, the choir, it made up to the fundamental needs of Christian liturgy. The Constantinian basilicas were characterized by a comparatively simple exterior and a magnificent interior, gleaming of guilding, marhle and mosaics, all in order to express the sovereignty of the Lord. Still being used is the instruction from Constantine to the bishop of Jerusalem, ordering him to make the Church of the Holy Sepulchre the most magnificent church in the world, thereby underlining the very special status of this monument of the Lord’s resurrection. Scholars have now reinterpreted the early documents and they hold that the basilica was actually intended to honour the holy Cross, hut probably Constantine the Great saw no fundamental difference between honouring the Cross and honouring the Holy Sepulchre; both signified victory to him. Four elements of the church interior proclaiming the message of Easter are to he considered: the orientation, the baptismal font, the altar, and the cross. Orientation From earliest times, Easter has been the cardinal point containing liturgical significance. This does not mean that the choir has always been situated in the eastern part of the church, hut in early Church, when the choir was often to be found in the western part of the building, mass was celebrated by the priest looking eastward. East is the cardinal point of the rising sun and the light, thereby symbolizing Christ himself and his resurrection. The Baptismal font The meaning of baptism is that the sinful human being is being buried and the renewed one is risen with Christ. The newly baptized have participated in the wonder of Easter.The font has been differently placed in the churches. In the early church, the not yet baptized were kept apart from the congregation and then baptized in separate baptistries before they were allowed to join the faithful. The baptistries were small, round or octogonal structures with a spring or hassin in the middle. The baptism took place at Easter, thus emphasizing its meaning of the death and resurrection of Christ.In medieval churches the font was situated in the western part of the church, opposite the choir and altar. The meaning of this arrangement was that baptism was necessary before the entering of the Church and the joining of the congregation. In Sweden a great number of medieval fonts are kept and still used, although they are now put in or close to the choir. In the pictorial decoration of these fonts, the resurrection is seldom depicted. In stead, scenes from Christ’s childhood and His own baptism are often to be found on the cuppa. Often, the lower parts of the fonts show symbols of evil, like dragons or monsters; there to frighten off the devil and dark powers from the font and the child. Rarely does the scene of resurrection occur on medieval fonts. One exception is the 12th century font from Ottravad, showing Christ risen, with a cross in his hand as a sign of victory. After the Reformation, the symbolism and meaning of interior architecture was no longer of importance and the location of the font varied from church to church. In the 19th and 20th centuries, the font was normally to he found in the choir, forming a triple together with the pulpit and the altar. The importance of God’s word and the Sacraments were thus to he pedagogically demonstrated to the congregation. Baptism was used for missionary purposes and the original meaning became somewhat obscured.In the 20th century, at least during the last decades, there has been a renewed consciousness of baptism, its meaning, and its connection with Easter celebration. In Easter liturgy, the baptismal vows are given by the attendants assembled around the font. In post-war church architecture the font has often been located in a place of its own, a kind of diminished baptistery within the church walls. The Altar The meaning of the altar is at the same time sacrifice - the sacrifice of Christ - and sacred meal in community with the risen Lord. The death and resurrection of Christ gives the altar its sacramental significance. The deco ration of the altar is the most important issue in a church’s interior, and often a summary of the creed of the congregation. In the 16th, 17th, and 18th centuries, the altar was often decorated with a monumental altarpiece representing, from below, the Last Supper, the Crucifixion, and the Resurrection. For the artists of the Baroque period the passion and death of Christ were closely related to His resurrection and victory. It is obvious that Swedish architects dealing with church interiors during the late 19th century - e.g. Helgo Zettervall, the author of a small book called General Instructions Concerning Church Building (title translated here), published in 1887 - repudiated the altar’s sacrificial dimension and underlined the symbolism of holy communion. The altar is not to be regarded as a postament of an altarpiece, though, especially not a Baroque one, according to Zettervall. Instead, he wanted the altar decorated or crowned with a huge crucifix image, in remembrance of the sacrifice of Christ, as he somewhat illogically wrote, which could sometimes be incorporated into a Gothic Revival triptych. The CrossThe Cross is the most important and central symbol within Christian culture, art, and architecture. Its deep significance is a result of its paradoxical message. It is, on the one hand, the depiction of an instrument of execution, and on the other hand it is a sign of victory and blessing.The ground-plan of a church is often shaped like a cross. But the ground' plan is mostly designed to fit functional aspects, and the cross shape is thus a kind of secondary effect. The exterior of a church can he crowned by a cross to make clear the character of the building. When entering a church, the visitor first beholds the crucifix hanging in the triumphal arch or decorating the altar.The narrative representations dominated in the Baroque altar-pieces. On paintings or reliefs the altar-piece showed the main scenes from the life of Christ, all dealing with redemption: the Incarnation or the Last supper, the Crucifixion, and the Resurrection. In Neoclassical churches this was not so any more. The most common altar decoration was an empty cross with symbols of Christ’s passion: the crown of thorns and the sepulchral clothes. These symbols have been discussed mostly as indications of rationalism and abstraction of the Christian faith, as a repudiation of the manifest and tangible. But they can on the other hand be interpreted as symbols of Christ’s resurrection: He has left the Cross and the crown of thorns - the symbol of degradation - with it, and also the sepulchral clothes, the ...